Nitrate removal, spatiotemporal communities of denitrifiers and the importance of their genetic potential for denitrification in novel denitrifying bioreactors. (October 2017) - Zhang, Yimin; Wang, Longmian; Han, Wei; Wang, Xu; Guo, Zhaobing; Peng, Fuquan; Yang, Fei; Kong, Ming; Gao, Yuexiang; Chao, Jianying; Wu, Dan; Xu, Bin; et al.
Highlights: Higher-rate NO 3 - -N removal is achieved in NUA–DNBF than in DAS–DNBF. The potential N2 O production rate was much lower in DAS–DNBF than NUA–DNBF. Burkholderiales, Rhodocyclales and Rhizobiales were dominant in both substrates. q nos Z and ∑q nir /q nos Z may serve as biological indicators for NO3 -N removal in DNBF. The NO 3 - -N removal rate in NUA increased linearly with the DEA. Abstract: Nitrate treatment performance and denitrification activity were compared between denitrifying biological filters (DNBFs) based on dewatered alum sludge (DAS) and neutralized used acid (NUA). The spatiotemporal distribution of denitrifying genes and the genetic potential associated with denitrification activity and nitrate removal in both DNBFs were also evaluated. The removal efficiency of NUA–DNBF increased by 8% compared with that of DAS–DNBF, and the former NUA–DNBF emitted higher amount of N2 O. Analysis of abundance and composition profiles showed that denitrifying gene patterns varied more or less in two matrices with different depths at three sampling times. Burkholderiales, Rhodocyclales, and Rhizobiales were the most commonly detected in both media during stable periods. Denitrification was determined by the abundance of specific genes or their ratios as revealed by controlling factors. The enhanced nitrate removal could be due to increasing q nos Z or decreasing ∑q nir /q nos Z. Furthermore, NUA–DNBF solely reduced nitrate by increasing the denitrification enzyme activity.